2019
DOI: 10.1186/s12929-019-0531-z
|View full text |Cite|
|
Sign up to set email alerts
|

Reactive oxygen species-dependent mitochondrial dynamics and autophagy confer protective effects in retinal pigment epithelial cells against sodium iodate-induced cell death

Abstract: Background Oxidative stress is a major factor in retinal pigment epithelium (RPE) cells injury that contributes to age-related macular degeneration (AMD). NaIO3 is an oxidative toxic agent and its selective RPE cell damage makes it as a reproducible model of AMD. Although NaIO3 is an oxidative stress inducer, the roles of ROS in NaIO3-elicited signaling pathways and cell viability have not been elucidated, and the effect of NaIO3 on autophagy in RPE cells remains elusive. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
62
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(65 citation statements)
references
References 31 publications
3
62
0
Order By: Relevance
“…The p38 mitogen-activated protein kinase (MAPK) activation is related to redox signaling transduction via stimulation of stress responses, including mitochondrial dysfunction [ 27 , 28 , 29 , 30 , 31 ]. Therefore, the protective antioxidant effect of chrysoeriol on the p38 MAPK pathway was determined in ARPE-19 cells.…”
Section: Resultsmentioning
confidence: 99%
“…The p38 mitogen-activated protein kinase (MAPK) activation is related to redox signaling transduction via stimulation of stress responses, including mitochondrial dysfunction [ 27 , 28 , 29 , 30 , 31 ]. Therefore, the protective antioxidant effect of chrysoeriol on the p38 MAPK pathway was determined in ARPE-19 cells.…”
Section: Resultsmentioning
confidence: 99%
“…However, we have observed different expression levels of inflammatory cytokines, IL-6, IL-1β, and TNF-α, in the presence of NaIO 3 in PTX3 shRNA expressing ARPE-19 cells compared with control shRNA expressing ARPE-19 cells (Figure S3). In a recent study, they found that NaIO 3 can induce cytosolic ROS but not mitochondrial ROS production and activate ERK, p38, JNK, and Akt signaling pathway [26]. Especially, they described that cytosolic ROS-dependent p38 and JNK activation lead to cell death in NaIO 3 -treated ARPE-19 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy is involved in a number of different processes in the retina participating in development and tissue remodeling and it is also implicated in photoreceptor cell death in response to calcium cytotoxicity, structural damage, and oxidative stress [35,47]. On the other hand, the aged retina is characterized by increased levels of reactive oxygen species (ROS), impaired autophagy, excessive energy consumption, and DNA damage, all of which contribute to the degeneration of RPE cells and link to AMD pathogenesis [48,49]. Besides, autophagy is not only linked to AMD but also to glaucoma, since dysregulation of autophagy can harm the outflow path of the trabecular meshwork, whereas promotion of autophagy via rapamycin treatment may have a cytoprotective effect upon oxidative stress [50].…”
Section: Autophagy and Oxidative Stressmentioning
confidence: 99%